2014
DOI: 10.1186/s40490-014-0006-7
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Phytophthora pluvialis to Pinus radiata and its relation with red needle cast disease in New Zealand

Abstract: Background: Red needle cast, a new foliage disease of Pinus radiata in New Zealand is described. The disease has been variable in incidence and severity both regionally and in different years. The early symptoms of discrete olive coloured lesions, often with a narrow dark resinous mark or band, were first recognised in winter of 2008 in plantation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
111
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(113 citation statements)
references
References 18 publications
2
111
0
Order By: Relevance
“…Suitable climatic regions for the persistence of P. ramorum and susceptible native hosts are widespread in Australia and New Zealand (Ireland et al 2013). Phytophthora pluvialis, a common and apparently benign species in western Oregon forests (Reeser et al 2013), has become a major pathogen of Pinus radiata in New Zealand (Dick et al 2014), but it has not been found on P. radiata within its native range in California. Also in New Zealand is the canker dieback of Kauri (Agathis austalis) caused by the newly described Phytophthora agathidicida, a pathogen of unknown origin (Weir et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Suitable climatic regions for the persistence of P. ramorum and susceptible native hosts are widespread in Australia and New Zealand (Ireland et al 2013). Phytophthora pluvialis, a common and apparently benign species in western Oregon forests (Reeser et al 2013), has become a major pathogen of Pinus radiata in New Zealand (Dick et al 2014), but it has not been found on P. radiata within its native range in California. Also in New Zealand is the canker dieback of Kauri (Agathis austalis) caused by the newly described Phytophthora agathidicida, a pathogen of unknown origin (Weir et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The causal pathogen has recently been described as Phytophthora pluvialis which is considered to be endemic to Oregon, USA (Reeser et al 2013). Subsequently, a second species Phytophthora kernoviae Brasier, Beales & Kirk, was also recovered from needles, though at a consistently lower rate (Dick et al 2014). Concurrent to epidemiological work for red needle cast, a range of trials were initiated to investigate possible fungicides that could be effective for management of red needle cast on Pinus radiata in New Zealand.…”
Section: Introductionmentioning
confidence: 99%
“…Observations of the symptoms, their development and the apparent spread of the disease, known locally as red needle cast, all gave a strong indication of a likely biotic cause, which led to further investigations. Isolations made from symptomatic needles yielded an undescribed species of Phytophthora as the likely causal pathogen (Dick et al 2014). The causal pathogen has recently been described as Phytophthora pluvialis which is considered to be endemic to Oregon, USA (Reeser et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, P. kernoviae has been found to naturally infect plants from 20 genera representing 13 families (Anon 2012;Dick et al 2014) in New Zealand and other parts of the world. Host plants are predominately angiosperms although three conifers, each from a different family, are also recorded hosts (Anon 2012;Dick et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Host plants are predominately angiosperms although three conifers, each from a different family, are also recorded hosts (Anon 2012;Dick et al 2014). Additional host species have been shown to be susceptible with artificial inoculations (Anon 2012, Fichtner et al 2012.…”
Section: Introductionmentioning
confidence: 99%